PERBEDAAN EFEKTIVITAS PENGGUNAAN JENIS MEDIA EDUKASI TENTANG ANEMIA TERHADAP PENGETAHUAN, SIKAP, EFIKASI DIRI REMAJA PUTRI DESA SIRNAGALIH - Alifah Safira Amperatmoko (LPPM Hang Tuah Pekanbaru, 2022)
Eﬀorts to prevent anemia in adolescent girls are significant to avoid the risk of abortion, low birth weight infant, the uterus cannot contract properly, and bleeding after delivery, resulting in death. Furthermore, one of the eﬀorts to prevent anemia in health promotion is by using learning media as a form of educational activity regarding anemia. This study aims to determine the diﬀerences in the eﬀectiveness of the use of educational media about anemia on the knowledge, attitudes, and self-efficacy of adolescent girls in Sirnagalih village. Moreover, the type of this study was quantitative with a quasi- experimental design - a non-equivalent control design. The sample number in this study was 60 people, obtained by the purposive sampling technique. The instruments used were pretest and post-test questionnaires. Meanwhile, the analysis used in this study was the Wilcoxon and Mann Whitney tests. The study results after health education are conducted show that there is a diﬀerence in the level of knowledge, attitudes, and self- efficacy of adolescent girls about anemia (p<0.005). The study's conclusion shows that video media is more eﬀective to be used as an educational medium about anemia for adolescent girls since, based on statistical tests, the average value of video media is higher than the average value of poster media.